ORGANIZATION OF CIRCLE WORK IN BIOLOGY CLASSES AT SCHOOL - Abdurasulova Kamola G‘afurovna.; Xolboboyeva Sarvinoz Temurbek qizi (Western European Studies, 2025)
The Organization of Circle work in biology classes at the school is important in increasing students ' interest in biology, deepening their knowledge, developing their practical skills and directing them to scientific research. The science of biology is aimed at studying nature, life processes, flora and fauna, and the role of Circle work is incomparable in order to strengthen its theoretical knowledge with practice. Through circles, students expand their knowledge to form independent thinking and research skills, which are of great help in their future educational and professional activities
Keywords: biology; knowledge; skills